Earnings Management, Financial Performance and Its Influence on Tax Avoidance with Independent Commissioners as Moderation - Galatio, Esterline; Trisnawati, Estralita (Jayapangus Press, 2024)
The exploration of the role between earnings management, financial performance (profitability), and their impact on tax avoidance is a compelling subject that hinges on perspective. This study aims to examine how earnings management and financial performance affect tax avoidance, with an independent commissioner serving as a moderating factor. Conducted as a quantitative analysis, the study focuses on non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022, using 80 companies as population, totalling 400 sample data to observe. Utilizing secondary data sourced from annual financial reports available on www.idx.co.id and individual company websites, the study employs a purposive sampling approach. Findings reveal that earnings management and financial performance significantly influence tax avoidance, while the presence of independent commissioners does not moderate the relationship between earnings management, financial performance, and tax avoidance.